Pengaruh akuntabilitas dan partisipasi masyarakat terhadap pengelolaan alokasi dana desa dalam pencapaian good governance pada desa di Kecamatan Air Batu - Siahaan, Plenskey Ivanovik Alexander; Widajantie, Tituk Diah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The research objectives in this study are: to prove the effect of accountability andcommunity participation on the management of village fund allocations in villages in AirBatu District. By applying the principles of good governance, it is hoped that it will supporthe recovery of the village economy, this can be created through labor-intensive programsdirect assistance from village funds, empowerment of MSMEs and agriculture, as well asdeveloping Village-Owned Enterprises and social safety nets. Furthermore, for thereformulation of distribution through performance strengthening. Finally, support thedevelopment of priority sectors through tourism villages, digital villages, fisheries andagriculture sectors, as well as improving health facilities. This type of research isquantitative research. The source of data in this study is the primary data source byconducting research and distributing questionnaires. The research sample was taken bypurposive sampling technique with the number of respondents as many as 48 people. Thedata analysis method used is multiple regression analysis. The hypothesis tester uses astatistical test tool, namely Partial Least Square (PLS) using Smart PLS 3.0 software. Theresults of the study indicate that accountability affects the management of village fundallocations, besides that community participation also affects the management of villagefund allocations. So that the principle of good governance is achieved in village government in Air Batu District.